The dose–response effect on polyphenol bioavailability after intake of white and red wine pomace products by Wistar rats. Issue 2 (7th February 2020) - Gerardi, Gisela; Cavia-Saiz, Mónica; Rivero-Pérez, M. Dolores; González-SanJosé, María Luisa; Muñiz, Pilar
Abstract : Wine pomace by-products are an important source of phenolic acids with health benefits and its bioavailability can differ between products and doses. Abstract : Wine pomace by-products are an important source of phenolic acids with significant health benefits. However, phenolic acid bioavailability in vivo has been little studied and there are few comparative studies on bioavailability between red and white wine pomace and the effect of intake of different doses. The qualitative and quantitative profile of phenolic acid metabolites in plasma and urine samples from Wistar rats was obtained by gas chromatography/mass detection, after oral administration of four doses (50, 100, 150, and 300 mg) of both the red and the white wine pomace products (rWPP and wWPP, respectively). The antioxidant capacity of the plasma samples assessed by both the ABTS and the FRAP levels was also evaluated. The results showed that neither the bioavailability nor the antioxidant capacity in vivo of the rWPP increased at high doses. However, both parameters were dependent on the intake of the wWPP.